2015
DOI: 10.1007/s00276-015-1441-8
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic artery arising from the anterior cerebral artery diagnosed by MR angiography

Abstract: Extremely rarely, the ophthalmic artery (OphA) arises from the A1 segment of the anterior cerebral artery (ACA). Discovery of this anomalous OphA during angiography or surgery has been reported in several patients. We report a case in which an OphA of ACA origin was diagnosed by magnetic resonance (MR) angiography and confirmed by selective cerebral angiography. To our knowledge, this is the first report of this variation with MR angiography. Careful observation of MR angiographic images is important for detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In this case, the OA enters the orbit through the superior orbital fissure or a duplication of the optic canal [25, 56]. The origin of the OA from the intracavernous ICA is usually referred to as the persistence of the PDOA [8, 63]. However, it has recently been observed that this interpretation was based on a misreading of Padget’s work [16].…”
Section: Variations Of the Oa Originmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the OA enters the orbit through the superior orbital fissure or a duplication of the optic canal [25, 56]. The origin of the OA from the intracavernous ICA is usually referred to as the persistence of the PDOA [8, 63]. However, it has recently been observed that this interpretation was based on a misreading of Padget’s work [16].…”
Section: Variations Of the Oa Originmentioning
confidence: 99%
“…The aberrant stemming from the anterior cerebral artery is another rare variant of the OA origin [3, 4, 18, 20, 21, 26, 28, 37, 63]. This variation has been frequently explained with the persistence of the PVOA [3, 4, 26, 28, 37, 63], though it more probably involves a persistent recurrent POlfA (Fig.…”
Section: Variations Of the Oa Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Extremely rarely, the OphA arises from the A1 segment of the ACA (Fig. 6.7) [9]. According to Padget [10], the ventral OphA arises from the cranial branch of the primitive ICA and migrates caudally to the normal position of the origin of the OphA.…”
Section: Opha Arising From the Anterior Cerebral Artery (Aca)mentioning
confidence: 99%
“…The anomalous origin can be from external carotid artery (ECA) branches, middle meningeal artery (MMA), ICA branches, anterior cerebral artery (ACA), basilar artery (BA) or posterior communicating artery (PcomA). 15 We are reporting the first case of bilateral ICA aneurysms with both side anomalous origin of OAs from MMA.…”
Section: Introductionmentioning
confidence: 99%